Rare Pseudotumor-like Hematoma at the Latissimus Dorsi Muscle Flap Donor Site: A Treatment Strategy Utilizing Negative Pressure Wound Therapy With Instillation and Dwell Time - Stumpfe, Maximilian C.; Horch, Raymund E.; Geierlehner, Alexander; Ludolph, Ingo (Wounds: A Compendium of Clinical Research and Practice, 2020)
INTRODUCTION: In reconstructive surgery, the latissimus dorsi (LD) muscle is known as a workhorse flap and is commonly used as a pedicled or free flap. Postoperative complications of a reconstructive procedure with an LD flap include seroma and hematoma formation at an early stage after LD transfer. Late-onset hematoma at the donor site are considered to be extremely rare postoperative complications; late, expanding pseudotumor-like hematoma can occur months or years after surgery. Shearing forces and poor coagulation are thought to be the primary reasons for these postoperative complications. CASE REPORTS: This report presents 2 cases of pseudotumors 12 and 29 years after LD transfer. Magnetic resonance imaging was performed prior to complete surgical excision. After surgical removal, patients received negative-pressure wound therapy with instillation and dwell time (NPWTi-d) for several days. After vacuum-assisted wound bed preparation, wound closure was performed with secondary sutures. CONCLUSIONS: The case report presented 2 incidences of rare late-onset pseudotumors many years after the initial LD reconstruction. To the authors' knowledge, this late-onset occurrence (ie, after 3 decades) has not been reported in the literature to date. If solidification of the late hematoma makes aspiration impossible, surgical intervention is required. Negative pressure wound therapy with instillation and dwell time potentially minimizes the wound size and reduces shear forces at the back donor-site.
CRIS-Team Scopus Importer:2021-04-19